2014
DOI: 10.1177/0886260514536281
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying, Low Self-Control, and Opportunity

Abstract: The theory of low self-control has been shown to be a valid predictor of a wide variety of criminal and deviant behaviors. However, a limited number of studies were conducted to understand the relationship between low self-control and bullying and the effects of opportunity factors (i.e., parental supervision, association with other bullies, negative school environment, and disciplinary measures used by teachers) on bullying in the context of low self-control theory. The present study, using a sample of nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 49 publications
8
68
0
5
Order By: Relevance
“…That is, the lower selfcontrol and the higher opportunities adolescents have, the more they commit online harassment. While Pratt and Cullen (2000) claimed that opportunity did not work well as a moderating predictor of deviance and crime, this study found the moderating effect between low self-control and opportunity on online harassment similar to previous research (LaGrange & Silverman, 1999;Longshore & Turner, 1998;Moon & Alarid, 2015;Seipel & Eifler, 2010;Smith, 2004).…”
supporting
confidence: 86%
“…That is, the lower selfcontrol and the higher opportunities adolescents have, the more they commit online harassment. While Pratt and Cullen (2000) claimed that opportunity did not work well as a moderating predictor of deviance and crime, this study found the moderating effect between low self-control and opportunity on online harassment similar to previous research (LaGrange & Silverman, 1999;Longshore & Turner, 1998;Moon & Alarid, 2015;Seipel & Eifler, 2010;Smith, 2004).…”
supporting
confidence: 86%
“…Explanations differ, some authors (Workman, 2012) suggest that impulsivity is a result of low self-control, and others found it to be a temporary characteristic for the-first-time Internet users and those seeking revenge (Korenis & Billick, 2014). Low self-control is also associated to SB perpetration (Moon & Alarid, 2015), and in a limited sample of children with ADHD victimisation (Unnever & Cornell, Running head: School-bullying and Cyber-bullying 2003). Low self-control can have both indirect (Vazsonyi et al, 2012) and direct (Marcum et al, 2014;You & Lim, 2016) effects on CB.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Lack of self control equals impulsivity (Archer & Southall, 2009). Low levels of self control in youth are also associated with the perpetration of physical and psychological bullying (Moon and Alarid, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing body of cross-sectional research on the link between drug use and bullying behaviour during school years (Brown, Riley, Butchart, & Kann, 2008;Moon & Alarid, 2014;Niemelä et al, 2011), no previous meta-analysis has been conducted to systematically synthesize relevant evidence and to identify the magnitude and the direction of this association. The current paper addresses this gap by meta-analysing results from existing published and unpublished studies following a comprehensive systematic review.…”
Section: Introductionmentioning
confidence: 97%